The effects of visual distraction following traumatic brain injury - Whyte, J; Fleming, M; Polansky, M; Cavallucci, C; Coslett, H B (Journal of the International Neuropsychological Society, 1998)
Clinical assessments of individuals with traumatic brain injury (TBI) typically report attentional difficulties, with distractibility prominent among these complaints. However, laboratory-based measures have often failed to find disproportionate distraction among patients with TBI, as compared to control participants. In this experiment, we tested 21 patients hospitalized for rehabilitation following recent TBI and 21 demographically comparable control subjects on a visual reaction time go-no-go task in which the target was preceded or followed by a brightly colored moving visual stimulus, appearing above the target location. Early distractors actually served as warning stimuli, improving accuracy and speed for both participant groups. Distractors occurring at or shortly after the time of target presentation had no significant impact on accuracy or response bias in either group, but did produce slowing of RT that was significantly greater for patients than for controls. The distractor that produced maximal slowing occurred 100 ms after the presentation of the target or foil. Repeated testing sessions led to reduction in the impact of the distractor and loss of the group difference in RT impact. The degree of RT slowing induced by distraction was modestly related to injury severity, as measured by the current score on the Disability Rating Scale, and the time until the patient first followed verbal commands. There was also a trend of greater RT slowing among individuals with focal orbitofrontal lesions, as assessed on neuroimaging studies. These results document a greater susceptibility to extraneous visual distraction among patients with TBI in comparison to controls. The fact that this difference appears only in the RT domain, and is greatest when the distractor follows the target, suggests that the primary impact of visual distractors is on response preparation and execution rather than target detection.